Numerical simulation of the thermal state and selecting the shape of air channels in heat-storage cells of electric-thermal storage. (November 2022) - Khimenko, Aleksei V.; Tikhomirov, Dmitry A.; Vasilyev, Alexey N.; Samarin, Gennady N.; Shepovalova, Olga V.
Abstract: Application of electric-thermal storage (ETS) in combination with energy generating equipment on the basis of renewable energy sources shall be considered as an effective concept, as well. This article deals with a numerical and experimental study of the thermal processes that take place in the heat charging and heat emission operation modes in ETS units. A two-dimensional numerical model for heat exchange processes adopted to ETS operation in the charging and heat emission modes has been developed. The role of the air channels' geometric parameters of heat-storage cells, air velocity in the channels and temperature difference on the temperature distribution in heat-storage cells and on the ETS operation efficiency during the charging and heat emission modes has been studied. The temperature distribution in heat-storage ETS cells during the charging and emission heat modes of ETS has been obtained, for air velocity in the channels of heat-storage cells in the range of 2 m/s to 3 m/s. Temperature values of air channels wall, that of heated air in the channels and the heat-transfer coefficient in the air channels of the heat-storage cells have been obtained. The energy-efficient design of the heat-storage cell having two round-shaped air channels has been proposed insuring a higher heat transfer in the air channels and reduces the ETS unit electricity consumption by 28%.